Perancangan Buku Informasi Kesenian Berokan Indramayu - Iis Purnengsih; Widya Nuriyanti; , Muhamad Saefullah (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
Berokan is a typical art from Indramayu played by a person who acts as the mainplayer using a costume made of burlap as a characteristic of Berokan art. IndramayuBerokan art is a cultural heritage of Indramayu which has a very important historicalstory, especially in the spread of Islam and da'wah in the Indramayu area. Informationthat conveys Barokan art is also still minimal, so not many people know the history ofBerokan. This study uses a qualitative descriptive method, where the data is in the formof primary data, namely direct observation of the Indramayu area and interviews withMr. Warnah the owner of the Berokan Wa'Aong studio located in Trisi Indramayu village,to dig deeper into the history of Indramayu Berokan art. Documentation and observationare carried out to find out the truth scientifically. Secondary data through literaturestudies as a solution to the problem, this study designs an information book on IndramayuBerokan Art aimed at the younger generation. This creation is based on the considerationthat information books are one of the media that are often used to obtain information,and knowledge and are suitable for conveying information about Berokan art.